2020
DOI: 10.1186/s12935-020-01306-8
|View full text |Cite
|
Sign up to set email alerts
|

LINC01094 triggers radio-resistance in clear cell renal cell carcinoma via miR-577/CHEK2/FOXM1 axis

Abstract: Background: Radioresistance is an obstacle to limit efficacy of radiotherapy. Meanwhile, long non-coding RNAs (lncRNAs) have been reported to affect radioresistance. Here, we aimed to investigate lncRNAs involving radioresistance development of clear cell renal cell carcinoma (ccRCC), the most frequent type of renal cell carcinoma (RCC). Methods: The mRNA and protein expressions of genes were measured via qRT-PCR and western blot. The relationships among genes were verified by RIP and luciferase reporter assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…LINC00460 promotes gefitinib resistance in non-small-cell lung cancer by targeting epidermal growth factor receptor by sponging miR-769-5p [21]. In clear cell renal cell carcinoma, LINC01094 can reportedly target the miR 577/CHEK2/FOXM1 axis, promoting radio resistance [22]. KEGG functional enrichment analyses elucidated the probable mechanisms of the high-risk group and low-risk group, but the specific mechanisms of ferroptosis-related lncRNAs in gastric cancer are fiendishly complex and still unclear, and this will be one focus of our future work.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00460 promotes gefitinib resistance in non-small-cell lung cancer by targeting epidermal growth factor receptor by sponging miR-769-5p [21]. In clear cell renal cell carcinoma, LINC01094 can reportedly target the miR 577/CHEK2/FOXM1 axis, promoting radio resistance [22]. KEGG functional enrichment analyses elucidated the probable mechanisms of the high-risk group and low-risk group, but the specific mechanisms of ferroptosis-related lncRNAs in gastric cancer are fiendishly complex and still unclear, and this will be one focus of our future work.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically, increasing evidence has revealed that lncRNA in the cytoplasm acts as a ceRNAs, which bind miRNAs to release such miRNAs targeted genes from degradation in human cancers [ 31 ]. In the previous studies, SNHG4, as a miR-377 sponge, was demonstrated to elevate the expression of ZIC5 in prostate carcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further study showed that lncRNAs can also effect the therapeutic response of ccRCC. Jiang et al showed that lncRNA 01094 induces radioresistance via regulation of the miR-577/CHEK2/ FOXM1 axis (13). Recently, the results of several studies have shown that lncRNAs also have a significant impact on the immune system in cancers such as triple-negative breast cancer, hepatocellular carcinoma (HCC), and glioblastoma multiforme (14)(15)(16), and these lncRNAs have been termed immune-related lncRNAs (irlncRNAs).…”
Section: Introductionmentioning
confidence: 99%